Monoclonal antibody and B-cell epitope mapping of the VP7 protein in bluetongue virus - Xin-Bing Hu; Jing Xu; Yu Zhang; Fan-Hua Meng; Zhan-Cheng Tian; Gui-Quan Guan; Jian-Xun Luo; Hong Yin; Jun-Zheng Du (Virology Journal)
Abstract Bluetongue virus (BTV) VP7 is a group-specific protein that is highly conserved in different serotypes. In this study, BALB/c mice were immunized with purified recombinant BTV-1 VP7 protein expressed in E. coli. Then six monoclonal antibodies (mAbs), 2A7, 2B2, 2B3, 2D3, 2D7, and 2H2, against the BTV-1 VP7 protein were produced using hybridoma technology. The reactivity of the mAbs was identified using western blotting, enzyme-linked immunosorbent assay, and immunofluorescence assay. A series of truncated peptides derived from VP7 expressed as glutathione S-transferase fusion proteins were mapped with mAbs by western blotting. The results indicated that 2A7 recognized the epitope 71SAAGINVGPI80, 2B3 recognized 110ARVTGETSTWG120, 2B2 and 2D3 recognized 125PYGFFLETEET135, and 2D7 and 2H2 recognized 332VNPMPGPLTRA342. Amino acid sequence analysis showed that these four epitopes were conserved in 24 typical BTV serotypes. Cross-reaction results showed that mAb 2A7 could recognize the recombinant VP7 protein of BTV-1, African horse sickness virus serotype 1 (AHSV-1), and epidemic hemorrhagic disease virus serotype 1 (EHDV-1). The mAbs 2B2, 2B3, and 2D3 could recognize the recombinant VP7 protein of BTV-1 and EHDV-1, and the mAbs 2D7 and 2H2 specifically recognized the BTV-1 VP7 protein. These specific mAbs and identified B-cell epitopes provided key insights into the structure and function of VP7, while facilitating the development of BTV diagnostics and the design of epitope-based vaccines.